Nilai Moral dalam Film Chalk N Duster Karya Jayant Gilatar serta Relevansinya untuk Pembelajaran Argumentasi Mahasiswa - Ammah, Erisy Syawiril; Al-Humairoh, Fuadilla Rahmah; Lestari, Sudarsri (INCARE, International Journal of Educational Resources, 2025)
The objective of this research is to analyze the moral values in the film "Chalk N Duster" by Jayant Gilatar and to examine its relevance for teaching argumentation to students. This research adopts a qualitative approach with a focus on library studies. The data analysis method is based on content analysis techniques integrated with semiotic theory. The semiotic analysis procedure specifically emphasizes two stages: the denotative and connotative meanings that emerge in the film's dialogues. The results of this study indicate that there are four forms of moral values: the moral value of courage, the moral value of generosity, the moral value of honesty, and the moral value of loyalty to the family. The moral values in the film "Chalk N Duster" can be used as a discussion material to train students in developing argumentation skills. By discussing the moral values in the film, students can learn to express opinions, defend positions, and understand other people's perspectives. This will enhance critical thinking and foster empathy and collaboration among peers.